Weight gain of pregnant sows associated with their behavior in pens and to the uniformity of piglets - Panzardi, Andrea; Mellagi, Ana Paula Gonçalves; Bierhals, Thomas; Gheller, Neimar Bonfanti; Bernardi, Mari Lourdes; Bortolozzo, Fernando Pandolfo; Wentz, Ivo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the association between the behavior of group-housed sows during feeding time, with weight gain during the last month of gestation and to determine if piglet birth weight uniformity is influenced by sow weight gain. Sows (n = 699) were separated into three parity groups (P): 2, 3–5, and 6–9. Each parity group was divided in three subgroups according to the percentage of weight gain: low, medium, and high. Sows from P 6–9 showed higher number of piglet birth weight below 1,200 g and higher birth weight coefficient of variation, in comparison to P 2 sows. Lower birth weight piglets and higher number of piglets weighing <1,200 g were observed in the low weight subgroup. There was a correlation of weight gain percentage during gestation with the number of visits to the feeder (r = 0.669) and with the number of aggressive encounters (r = 0.451). Variation in weight gain during the last month of gestation in group-housed sows is influenced by competition at feeding time, and the lower weight gain during the last month of gestation reduces the birth weight of piglets.